2015
DOI: 10.1111/papr.12334
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Chronic Pain in a Large Integrated Healthcare Delivery System in the U.S.A

Abstract: In this comprehensive analysis of 2 years of data from a large, vertically integrated metropolitan health system, chronic pain was identified in 12% of adult patients. Approximately 75% of chronic pain conditions were musculoskeletal. The triad of age ≥ 60 years, BMI ≥ 30, and female sex were the most salient demographic characteristics of patients with chronic pain conditions. These diagnostic and demographic data may be used to inform treatment program development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Employees were included in the other chronically painful conditions (control) cohort if they had two or more treatment claims with a diagnosis for a pre-specified painful condition at least 30 days apart. 31 Employees not meeting the criteria for either cohort were excluded. For the purposes of developing statistical weights and controlling for confounding characteristics (described below), we created an indicator variable for each of the conditions included in the control cohort.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Employees were included in the other chronically painful conditions (control) cohort if they had two or more treatment claims with a diagnosis for a pre-specified painful condition at least 30 days apart. 31 Employees not meeting the criteria for either cohort were excluded. For the purposes of developing statistical weights and controlling for confounding characteristics (described below), we created an indicator variable for each of the conditions included in the control cohort.…”
Section: Methodsmentioning
confidence: 99%
“…Employees were included in the OA cohort if they had two or more treatment claims with primary or supplemental diagnoses of OA. Employees were included in the other chronically painful conditions (control) cohort if they had two or more treatment claims with a diagnosis for a pre-specified painful condition at least 30 days apart 31 . Employees not meeting the criteria for either cohort were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Identification of patients has been previously described as part of an epidemiologic evaluation of chronic pain, but in brief, patients were identified based on the presence of ≥ 2 ICD‐9‐CM codes at least 30 days apart for the conditions of interest during the study period of January 1, 2010 to December 31, 2010. Choice of conditions was derived from a study by Davis et al supplemented by conditions additionally identified as being of interest by the investigators, for a total of 24 chronic pain conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Musculoskeletal pain is prevalent among workers and working-age adults 1–3 . It is also a leading reason for worker compensation 4 and disability claims 5,6 .…”
mentioning
confidence: 99%